Refabricating Individualism and Commodifying Anti-Capitalism: Melodramatic SF and VOD Spectatorship. - Sebastián-Martín, Miguel (Science Fiction Studies, 2021)
This essay analyzes certain audio-visual sf narratives that are primarily distributed via VOD (video-on-demand) platforms, specifically focusing on episodes of Netflix’s Black Mirror and Amazon’s Electric Dreams, considering both in the context of postcinematic spectatorship. It shows how the ostensibly subversive, anti-capitalist narratives of these shows may lead towards conformity with hegemonic individualism, especially when viewed through VOD platforms. The underlying assumption is that the possibility of subversion is dialectically entwined with—yet not necessarily annulled by—its recuperation by dominant neoliberal individualism, which makes each of these series ambiguously open-ended in their ideological effects. Although this essay centers upon two examples within their specific context of reception, it also suggests a larger theoretical framework for the understanding of similar forms of contemporary sf, proposing “melodramatic science fiction” as an analytic lens that incorporates and reframes ideas originally developed for the criticism of melodrama.